Is Increased Ideological Distance From One's Congresspeople Associated With Increased Self-Identification as an Independent? - Mankoff, Bradley (Journal of Management Policy and Practice, 2021)
While much research studies what political attitudes and political behaviors distinguish American nonpartisans (“Independents”) from partisans, little research has investigated what environmental factors in an individual’s life are associated with self-identification as an Independent. This paper begins that investigation by testing whether a rudimentary measure of distance of oneself from one’s congresspeople is positively associated with one’s probability of self-identifying as an Independent. Seminal research from social psychology about the availability heuristic and social desirability bias combined with Klar’s and Krupnikov’s insights about a general aversion to partisan labels provide the theoretical framework for my hypothesis. Individuals’ ideologies are taken from self-reports from the CCES cumulative file (~424,000 respondents), and congresspersons’ ideologies are taken from DW-NOMINATE. I find a modest positive association between distance and independent-identity, however the inconsistency of that result across different ideologies and across the House and Senate leads me to doubt the substantive significance of my findings. A panel study or experiment could better test my hypothesis.